Analysis and Evaluation of the Role of Mass Media on Urban Branding in Tourism - Yazdani, Mohammadhasan; Alipour, Ebrahim; Dashti, Amir Hesam; Arzhengi, Bahram (Civil Engineering Journal, 2018)
One of the Provinces competitiveness components in attracting tourists is the urban tourism branding and one of the most influential factors in this field is advertising and informing through the mass media which was a key point and the main goal in this research. This is of applied type in terms of purpose and research and describes the correlation between variables and is a survey way in terms of research method. The statistical sample of this study was 371 people who were selected by stratified random sampling. Finally, the data were analyzed by SPSS software and the variables were evaluated by AHP and ANP methods. The results of the pair comparison of the criteria indicated that the media advertising with the coefficient of 0.3352 has priority over other criteria for urban tourism development based on urban branding. Interpretation of the results of the standardized regression coefficients, namely beta (Beta), showed that the representation of tourism places in the form of tangible facts with beta of 289.0 had the greatest impact on the variable of tourism development and the establishment of urban branding. Therefore, a standard deviation in the representation variable increased the development rate of tourism by a standard deviation of 289.0, on the contrary.